Synergetic effect of silver molybdenum tungsten oxide heterostructures for enhanced photocatalytic reaction - Shomaila Khanam; Sanjeeb Kumar Rout (Chemical Physics Impact, 2022)
A plasmonic Ag/MoxW1-xO3-y heterostructure was synthesised using a solvothermal followed by photodeposition method. The resulting plasmonic Ag/MoxW1-xO3-y heterostructure displayed high localised surface plasmon resonance (LSPR) after detailed characterisation by using XRD, XPS, TEM, and UV–Vis measurements. The high LSPRs were attributed to crystal vacancies, particularly mutual doping vacancies of molybdenum and tungsten ions, as well as oxygen vacancies. We also investigated into whether such plasmonic Ag/MoxW1-xO3-y might be employed as a highly efficient catalyst for ammonia borane (NH3BH3; AB) dehydrogenation and catalytic destruction of RhB and MB under visible light irradiation as well as in dark condition. As a result when irradiated by visible light for 120 min, it yielded 24 μmol/min of H2 and was very effective in destruction of organic dyes, degrading 90% of RhB and 98% of MB within 40 min. This efficiency was not achieved by MoO3, WO3 or MoxW1-xO3-y alone. These results demonstrates that Ag/MoxW1-xO3-y is a promising a candidate for hydrolysis of ammonia borane and destruction of RhB and MB.